Miniaturization of a Broadband Quadrature Hybrid Coupler Using ?-Model Transformation-Based Artificial Transmission Line - Nejad, Vahid Iran; Lotfi-Neyestanak, Abbas Ali; Shahzadi, Ali (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a novel compact broadband quadrature hybrid coupler based on planar artificial transmission line is presented. This coupler can be used for WLAN application at 2.4 GHz. The planar artificial transmission line has been implemented using ?-model technique. The size of the proposed coupler is merely 38% of that of a conventional one. The compact coupler performs well wideband response.